A DESCRIPTIVE STUDY ON THE READING ABILITY OF THE SECOND YEAR STUDENTS OF SLTP ISLAM SUDIRMAN TENGARAN SEMARANG IN 2005 / 2006 ACADEMIC YEAR - Hendarini , Renny Dwi (2007)
Reading is not a single skill but it involves a variety of skills, they are: (1) recognizing the script language, (2) deducing the meaning and use of unfamiliar lexical item, (3) understanding explicitly stated information, (4) understanding information when not explicitly stated, (5) understanding conceptual meaning, (6) understanding the communication value (function) of sentence and utterances, (7) understanding relations within the sentence, (8) understanding relation between the parts of a text through lexical cohesion devises, (19) understanding cohesion between part a text through grammatical cohesion devises, (10) interpreting text by going out side it, (11) recognizing indicators in discourse, (12) distinguishing the main idea from supporting details, (13) extracting silent points to summarize, (14) selective extraction of relevant points from a text, (15) basic reference skills, (16) skimming, (17) scanning to locate specifically required information, and (18) Transco ding information to diagrammatic display. This study aims at describing the reading ability of the second year students of SLTP Islam Sudirman Tengaran Semarang and finding the most difficult skill faced by the students. To collect the data the writer uses observation and reading test. The data are analyzed by using simple statistic and described the result of calculation. The writer uses random sampling to take the subject of the study. The descriptive analysis study is used in this study. It is started with describing the data, and analyzing the data to find out the conclusion of the study. The result of study shows that the mean score is 59.34%. It belongs to fair level. So the writer concludes the reading ability of the second year students of SLTP Islam Sudirman Tengaran Semarang is fair and the most difficult skill faced by second year student is understanding the communicative value (function) of sentences and utterances.